Expert Lecture and Live Demo: The Latest Endodontic Treatment and Restoration with Dental Fiber Posts - Nina Djustiana; Elin Karlina; Zulia Hasratiningsih (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Endodontic treatment of anterior trauma and caries followed by post and crown restoration is not included in the minimum standard of oral care in primary health facilities. Endodontic treatment, which requires a relatively long time and the number of visits compared to mere tooth extraction, often makes it impossible to carry out in a health facility with many patients per day. This community service was aimed to provide technical understanding and knowledge of endodontic treatment procedures for anterior teeth that are simple, up-to-date, with a minimum number of visits, and provide an understanding of the selection of dental fibre post materials that meet reasonable material requirements at a more affordable price. Methods for implementing the activities consisted of: (1) Formulation and preparation; (2) Pre-test; (3) Expert lecture; (4) Live demo; and (5) Post-test. This community service increased the knowledge and ability in endodontic treatments for anterior teeth and their restoration with dental fibre posts from the prospective dentists and dentists who were participants in this community service. This activity can also lead to the making of the latest manual and standards for endodontic treatment for anterior teeth and their restoration with dental fibre posts.